2016
DOI: 10.1016/j.jpainsymman.2015.12.332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short-Term Dance Movement Therapy Program on Symptoms and Stress in Patients With Breast Cancer Undergoing Radiotherapy: A Randomized, Controlled, Single-Blind Trial

Abstract: The short-term DMT program can counter the anticipated worsening of stress and pain in women with breast cancer during radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
113
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 32 publications
4
113
0
2
Order By: Relevance
“…20 The findings of this study are similar to those observed when using tango therapy in people with self-reported depression 26 and dance therapy with depressed adult patients. 17 These results are also consistent with those reached using dance movement therapy in patients with cancer, as shown by Ho et al, 43 or those obtained by Bräuninger 32 in people with stress. However, both studies obtained a smaller effects size.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…20 The findings of this study are similar to those observed when using tango therapy in people with self-reported depression 26 and dance therapy with depressed adult patients. 17 These results are also consistent with those reached using dance movement therapy in patients with cancer, as shown by Ho et al, 43 or those obtained by Bräuninger 32 in people with stress. However, both studies obtained a smaller effects size.…”
Section: Discussionsupporting
confidence: 76%
“…However, both studies obtained a smaller effects size. These and other studies 20,32,43 demonstrate that dance movement therapy may reduce emotional distress by improving emotion-oriented coping strategies, the ability to interpret emotions, self-confidence, and affect. On the contrary, another study 35 using Biodanza did not show significant improvements in the depression levels of fibromyalgia patients.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations